Synthesis and characterization of starch / silica nanocomposite from native corn and tapioca starches - Raja Mohd. Raffel, bin Zulkifli (Faculty of Resource Science and Technology, 2008)
Both corn and tapioca starches are common sources of food in our lives. These two types of starches are important raw materials for manufacturing monosodium glutamates, fiuctose, glucose and dextrose. The aim ofthis study is to utilize the native starches for the preparation of nanostructured starch/silica composites. This study involves preparation of starch sponges from both types of the starches and characterize them using established characterization techniques. These starch sponges were mixed with silicon dioxide nanoparticles to form starch/silica nanocomposites. These nanocomposites were further heated under controlled conditions to form carbon/silica nanocomposite or nanostructured silica xerogels. The physical and chemical properties of these nanocomposites and xerogels were characterized by standard characterization techniques.